2008
DOI: 10.1073/pnas.0802597105
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of origination and extinction in the marine fossil record

Abstract: The discipline-wide effort to database the fossil record at the occurrence level has made it possible to estimate marine invertebrate extinction and origination rates with much greater accuracy. The new data show that two biotic mechanisms have hastened recoveries from mass extinctions and confined diversity to a relatively narrow range over the past 500 million years (Myr). First, a drop in diversity of any size correlates with low extinction rates immediately afterward, so much so that extinction would almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
489
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(521 citation statements)
references
References 63 publications
23
489
4
5
Order By: Relevance
“…The Jurassic-Cretaceous boundary was earlier considered to be one of the major mass extinction events during the Phanerozoic (Sepkoski and Raup, 1986) with groups such as corals, brachiopods, bivalves, ammonites and fish all affected. As noted above, subsequent work has downgraded the boundary to a minor extinction event at most (Alroy, 2008). However, some recent studies have found evidence for a real diversity trough within terrestrial dinosaurs and marine reptiles (e.g., Mannion et al, 2011).…”
Section: Comparison and Interpretation Of δ 13 C Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jurassic-Cretaceous boundary was earlier considered to be one of the major mass extinction events during the Phanerozoic (Sepkoski and Raup, 1986) with groups such as corals, brachiopods, bivalves, ammonites and fish all affected. As noted above, subsequent work has downgraded the boundary to a minor extinction event at most (Alroy, 2008). However, some recent studies have found evidence for a real diversity trough within terrestrial dinosaurs and marine reptiles (e.g., Mannion et al, 2011).…”
Section: Comparison and Interpretation Of δ 13 C Trendsmentioning
confidence: 99%
“…This is, in part, due to the lack of an agreed upon, chronostratigraphic framework for the Jurassic-Cretaceous boundary (Zakharov et al, 1996;Wimbledon et al, 2011;Michalík and Reháková, 2011;Guzhikov et al, 2012;Shurygin and Dzyuba, 2015). It is a time of contentious biotic changes, for which opinions have ranged from proposal of a putative mass extinction (Raup and Sepkoski, 1984) or a regional event (Hallam, 1986) or nonevent (Alroy, 2008;Rogov et al, 2010). Using large taxonomic occurrence databases, several recent studies (particularly of tetrapods) have re-examined the Jurassic-Cretaceous boundary, and note a sharp decline in diversity around the Jurassic-Cretaceous boundary (Barrett et al, 2009;Mannion et al, 2011;Upchurch et al, 2011;Tennant et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Triassic-Jurassic boundary (TJB) is preceded by one of the five largest Phanerozoic 58 biotic crises, the end-Triassic extinction (ETE) (Alroy, 2008;Raup and Sepkoski, 1982), 59…”
Section: Introduction 57mentioning
confidence: 99%
“…Jelenlegi ismereteink szerint a triász időszakot lezáró tömeges kihalás a fanerozoikum egyik legnagyobb kihalási rátájával jellemezhető eseménye volt (ALROY 2008(ALROY , 2014. Az ökológiai szempontból kedvezőtlen hatások, mint a glo bális felmelegedés és az óceán savasodása (l. alább) első sor ban a tengeri ökoszisztémát sújthatták, továbbá az ős ma radványok megőrződésének feltételei is jellemzően a ten ge rekben kedvezőbbek.…”
Section: Változások Az éLővilágbanunclassified